A Chiroptical Probe for Sensing Metal Ions in Water12. Issue 27 (5th August 2013) - Caricato, Marco; Leza, Nerea Jordana; Roy, Kinkini; Dondi, Daniele; Gattuso, Giuseppe; Shimizu, Linda S.; Vander Griend, Douglas A.; Pasini, Dario
Abstract: We describe a novel Binol‐containing macrocycle that behaves as a chiroptical probe for the detection of biologically relevant ions (Cu 2+, Zn 2+ ) under physiological conditions. The macrocycle synthesis is carried out with Binol‐based synthons suitably derivatized in the 2, 2′‐ and 3, 3′‐positions, by means of a room temperature esterification reaction as the cyclization procedure, followed by late‐stage unmasking of the four carboxylic acid functionalities embedded within the macrocyclic framework. The recognition events, signaled using both UV and CD spectroscopy, are triggered by macrocyclic rearrangement induced by binding of the cations through coulombic interactions with the carboxylate anions in water at pH 7. The ample CD response ensures high chiroptical sensitivity and demonstrates the feasibility of chiroptical detection of biologically relevant cations by using a non‐nitrogen‐based ligand under aqueous conditions. Abstract : A Binol‐containing macrocycle behaves as a chiroptical sensor for the detection of biologically‐relevant transition‐metal cations in buffered aqueous solution.